HARNESSING CRISPR FOR CONSERVATION: GENE EDITING AS A TOOL FOR BIODIVERSITY PRESERVATION IN THE FACE OF CLIMATE CHANGE - Hossam El-Khatib (Modern American Journals, 2025)
The rapidly escalating impacts of climate change on biodiversity have highlighted the need for innovative conservation strategies. Among the most promising advancements is the use of CRISPR-Cas9 gene editing technology, which allows for precise modifications to the genetic makeup of organisms. This paper explores the potential of CRISPR as a tool for biodiversity preservation in the face of climate change, focusing on its applications in species adaptation, restoration of genetic diversity, and mitigation of extinction risks. We examine the ethical, ecological, and practical considerations of using gene editing for conservation, alongside case studies of successful and ongoing projects. While CRISPR holds considerable promise for combating the impacts of climate change on ecosystems, careful regulation and monitoring are necessary to ensure that its use does not inadvertently disrupt the balance of natural systems.
Keywords: CRISPR, Gene Editing, Conservation, Climate Change, Biodiversity, Genetic Diversity, Species Adaptation, Ethical Considerations, Ecosystem Restoration, Biotechnology